Public Service Through the provision of Tourist Route Instructions in the Integrated Ampel Tourism Area of Surabaya City - Dandi Darmadi; Muhammad Indrawan Jatmika; Anggie Parawitha Lucca (Future Science, 2022)
The Ampel Tourism Area is one of the leading tourist destinations for the Government and the City of Surabaya. As a religious and historical destination, the Ampel Tourism Area has characteristics and uniqueness that have become an attraction and a challenge in the development and management of both government and community officials. This uniqueness is characterized by the diversity of policy makers' backgrounds and geographical challenges as a cultural heritage with small alleys and narrow alleys as characteristic of tourism object backgrounds. For this reason, in developing tourism areas, it is necessary to develop and make integrated public policies to encourage the development of tourism objects that are beneficial for the progress of the community. The purpose of this community service is to encourage integration in tourism management in the Ampel Tourism Area through the assistance of integrated public service governance with collaborative governance strategies in the tourism sector and the provision of tourism-supporting facilities in the form of road signs. Collaborative Governance encourages policy stakeholders to reach a consensus on tourism decision-making facilitated by non-governmental actors in a formal, consensus-oriented, and consultative collective policy-making process to make or implement public policies and manage programs or assets. Public. This policy will be implemented by providing and installing road signs around the Ampel Area. The provision and installation of road signs are considered essential to overcome the problems of historical and religious tourism objects with unique characteristics while simultaneously encouraging the integration of Ampel areas with interactions between tourists, local communities, small business actors, and policymakers.